(untitled) (Revista científica Olimpia, 2025)
The article presents the social need for research, technologies and innovation in the prioritized and differentiated attention of the primary level teacher aimed at addressing the diversity in students with whom they systematically interact, recognizing the advantages and opportunities they provide as a contributing element. To the improvements of scientific research, the objective is to design a strategy for the professional improvement of primary level teachers aimed at attention to diversity in those educated in conditions of inclusion. The approach used in the research is mixed with a correlational scope where the dimensions and indicators are assumed and contextualized, the cause-effect relationships were established between the variables of the professional improvement of primary level teachers and the knowledge to be acquired about care. to diversity in those educated in conditions of inclusion, methods related to critical opinion and collective construction workshops were used with the team of experts with mastery of the topic, the study of qualitative data from diverse sources, documentary analysis and the systematic review of literature. Being appropriate to implement a strategy for professional improvement of primary level teachers, the feasibility of the proposal is shown, validated through critical opinion workshops, collective construction, which allows the improvement of their practice, capable of raising the educational quality and dignity of the students. learners in conditions of inclusion.